In Search of Infall Motion in Molecular Clumps. V. HCO+ (1–0) and HCN (1–0) Observations toward 210 Infall Candidates - Shuling Yu; Zhibo Jiang; Zhiwei Chen; Yang Yang; Haoran Feng (The Astronomical Journal, 2024)
We have carried out HCO ^+ ( J = 1–0) and HCN ( J = 1–0) line observations towards 210 infall candidates selected from the CO blue-profile catalog by Jiang et al., using the Purple Mountain Observatory 13.7 m telescope. Out of the 210 targets, 42 sources are further confirmed to have infall signatures in HCO ^+ and/or HCN lines, with a confirmation rate of ∼20%. According to the line profiles, we classify them into two categories: double-peaked and peak-shoulder. Some physical properties are estimated through profile fitting using the RATRAN model. We find that the two types are separated in parameter space, indicating they may be of different properties. The median values of kinetic temperature, infall velocity, and mass infall rate for the two types are 10.5 K and 40.8 K, 0.40 km s ^−1 and 1.00 km s ^−1 , and 4.6 × 10 ^−5 M _⊙ yr ^−1 and 3.5 × 10 ^−4 M _⊙ yr ^−1 , respectively. The infall velocities and mass-infall rates of peak-shoulder sources are slightly larger than those of double-peaked ones, suggesting they tend to form more massive stars. We also discuss the association of the 42 confirmed sources with other star formation activities such as maser and outflow, which supports this result.